Association between Diethylhexyl Phthalate Exposure with Folliculogenesis and Ovarian Steroidogenesis: A Systematic Review and Meta-Analysis - Weihuan Hu; Yan Wu; Yuhang Zhu; Fangfang Wang; Fan Qu (Clinical and Experimental Obstetrics & Gynecology)
Background: Environmental endocrine disruptor-diethylhexyl phthalate (DEHP) or its active metabolites-mono(2-ethylhexyl) phthalate (MEHP) has the greatest endocrine disrupting potency. The present systematic review and meta-analysis was to investigate the effects of DEHP/MEHP exposure on the folliculogenesis and ovarian steroidogenesis in female rodents. Methods: A search was conducted using EMBASE, PubMed, Web of Science, and Cochrance Library databases. The meta-analyses were performed using mean difference (MD) and random-effects model. Risk of bias and subgroup analyses were assessed using Revman 5.4.1 and R 4.1.2. Registration number: PROSPERO CRD42021292264. Results: A total of 15 studies were included in this systematic review. We found that the exposure of DEHP/MEHP significantly increased the ovary weight (p = 0.003), decreased the serum progesterone levels (p = 0.0008) and delayed the vaginal opening (p = 0.01). Conclusions: The DEHP/MEHP exposure has adverse effects on some aspects of female reproduction ability which tested in female rodent. However, more evidence is needed to strengthen the conclusion.